In-country availability of medical abortion medicines: a description of the framework and methodology of the WHO landscape assessments - Ulrika Rehnström Loi; Ndola Prata; Amy Grossman; Antonella Lavelanet; Natalie Williams; Bela Ganatra (BMC, 2023)
Plain Language summary Increasing availability of affordable, safe, and effective medical abortion medicines is necessary to improve access to safe medical abortion services. Driven by the results of a meeting hosted by the World Health Organization and the Swedish International Development Cooperation Agency in 2018, we decided to examine access to medical abortion medicines from supply to demand in selected countries. The overarching goal of the national landscape assessments was to generate evidence to support advocacy efforts and policymaking that is appropriate to the needs of the country. This paper aims to describe the assessment protocol and the steps taken in the World Health Organization landscape assessments of medical abortion medicines at country-level. The assessment allows for a determination of the enabling environment surrounding the provision of medical abortion services. This in turn allows for the identification of key barriers that limit availability of abortion medicines, and the identification of opportunities to overcome those barriers. The availability framework includes both supply and demand sides of commodity availability, considering factors from product introduction to use. This approach can be used for future national assessments for any health commodity or service. The assessment findings will be informative to policymakers and programme managers in developing plans to safeguard availability of safe and effective medical abortion medicines.